Analise do comportamento mecanico do poli(acido l.actico) em amostras impressas em 3D para aplicação em implantes ortopedicos - Monteiro, Macleane Ferreira Leite (Universidade Federal Rural do Semi-Árido, 2021)
The 3D p1inter is equipment capable of developing and manufacturing parts by modeling them in appropriate software, where imagination is the limit for creation. One of the materials used by these printers is Poly(lactic acid) or PLA, a biodegradable polymer with infinite capacity for creation if used in this equipment, however, little is known about its mechanical characteristics and whether its use has applications in different Study areas. Based on this idea, this work aims to pe1form static strength and stiffness tests, where printed specimens are subjected to traction and compression, and analyze the results with the Digital Image Correlation (CDI) method. In addition to the mechanical analysis of the material, the work also has the question of whether it is possible to use the printer with this polymer for application in medicine, more specifically in the orthopedic sector.
Keywords: Impressora 3D; Poli(Acido Lactico) PLA; Correlação Digital de Imagens (CDI); Ensaios mecanicos; Ortopedia; CIENCIAS EXATAS E DA TERRA::CIENCIA E TECNOLOGIA